Effect of Contamination by Fungi and Yeast on the Physiochemical Characteristics of Gum Arabic Stored in Semi-Desert Climate of Khartoum City, Sudan - Adam, Fathia A; Abdellah, Abdelmonem M; Abdel-Magid, Hago M; Osman, Mohamed E (Journal of Food Technology Research, 2016)
Structural properties of gum Arabic are one of the most important factors affecting the competitive prices in the domestic and overseas markets. Using laboratory standard methods, a number of methods were used to characterize the main alterations of the components of Acacia Senegal var. Senegal gum Arabic induced by inoculation with some species of fungi and yeast. Results revealed that, depending on the inoculated microbial species, the pH, viscosity, nitrogen and protein were decreased to various levels. The sugars content has noticeably been affected viz. galactose was entirely consumed by Saccharomyces cerevisiaeand Penicilliumnotatum while .rhamanose was drastically decreased by all microbial species under study. Likewise, the number average molecular weight was decreased by all species. Therefore, it may be concluded that the factors encouraging microbial growth must be given due consideration under gum Arabic storage conditions.